Entrepreneurship of Traditionalist Muslim at Tasikmalaya, West Java - Yadi Janwari (International Journal of Nusantara Islam, 2013)
The difference of religious understanding does not have a significant relationship with economic behavior, especially entrepreneurship. The difference of religious understanding to traditional understanding and modern understanding becomes no longer significant to be associated with economic behavior. This means that the study of economic behavior associated with the difference of religious understanding to traditional understanding and modern understanding is very biased. This is because the most decisive variable in understanding the flow of economic behavior is not religious understanding, but rationality in economic decisions taken based on traditions, values, and straightforward arguments. This study have different conclusion with finding of Max Weber, Robert N. Bellah, David C. McClelland, and Clifford Geertz theories, in the context of socio-economic disciplines which states that there is a correlation between modern religious understanding and economic behavior. Their conclusion were not true base on is the fact that people who have an understanding of modern religious relate to economic behavior. In fact, based on this research, religious understanding that relates with economic behavior is precisely traditional religious understanding. Variables that determine the flow of economic behavior is not a religious understanding, but the rationality in economic behavior. Therefore, the emphasis of the conclusions formulated by Max Weber, Robert N. Bellah, David C. McClelland, and Clifford Geertz is not in its modern religious ideas, but in the rationality held by economic actors. Their conclusion may be justified if there is any further explanation that the modern religious understanding is rational and has implications for other aspects of life, including the aspect of economic activity. Besides, their finding could not generalized and gone into effect to other place owning different characteristic.